A Prospective Randomized Trial Comparing a Combined Regimen of Amikacin and Levofloxacin to Levofloxacin Alone as Prophylaxis in Transrectal Prostate Needle Biopsy. - Miyazaki, Yu; Akamatsu, Shusuke; Kanamaru, Sojun; Kamiyama, Yuki; Sengiku, Atsushi; Iguchi, Ryo; Sano, Takeshi; Takahashi, Akira; Ito, Masaaki; Takenawa, Jun; et al. (Urology Journal, 2016)
Purpose: We investigated whether addition of amikacin to levofloxacin-based antimicrobial prophylaxis reduces febrile urinary tract infections after transrectal ultrasound-guided prostate needle biopsy (TRUSB). Materials and Methods: A total of 447 patients undergoing TRUSB were prospectively randomized into two groups. The 230 patients in Group A were given one oral dose of levofloxacin 400 mg prior to TRUSB; the 217 patients in Group B each received the same dose of levofloxacin and one 200 mg intravenous dose of amikacin. Patients’ characteristics were assessed prior to TRUSB and their symptoms were checked after the TRUSB. Results: Both regimens were well tolerated with no side effects. No statistically significant difference in patients’ characteristics, or in incidence of inflammation- or infection-related symptoms was seen between the two groups; nor any significant difference among those who developed fever and those who did not. Two Group A patients and one Group B patient developed febrile urinary tract infections. Accountable pathogens determined by urine and blood cultures were fluoroquinolone-resistant E.coli and extended-spectrum β-lactamase-producing E.coli. All pathogens isolated were levofloxacin-resistant, amikacin-susceptible species. Conclusion: Although the present study was under-powered by unexpectedly low overall incidence of febrile urinary tract infections, addition of one intravenous administration of amikacin to one oral administration of levofloxacin showed no advantage compared with levofloxacin alone as antimicrobial prophylaxis in TRUSB. Strikingly, all pathogens isolated from febrile patients were sensitive to amikacin in vitro. Therefore, further understanding of amikacin’s drug kinetics in the prostate is necessary to develop a more efficient drug delivery system for amikacin.